2020
DOI: 10.1007/s40520-020-01551-x
|View full text |Cite
|
Sign up to set email alerts
|

Frailty, walking ability and self-rated health in predicting institutionalization: an 18-year follow-up study among Finnish community-dwelling older people

Abstract: Background In clinical practice, there is a need for an instrument to screen older people at risk of institutionalization. Aims To analyze the association of frailty, walking-ability and self-rated health (SRH) with institutionalization in Finnish community-dwelling older people. Methods In this prospective study with 10-and 18-year follow-ups, frailty was assessed using FRAIL Scale (FS) (n = 1087), Frailty Index (FI) (n = 1061) and PRISMA-7 (n = 1055). Walking ability was assessed as self-reported ability to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 35 publications
3
32
1
Order By: Relevance
“…By omitting the participants still living at home at the end of the follow-up period, we also ascertained that we had complete data on the participants’ acquired conditions during their lifetime. The excluded participants were, however, in better health than the included participants and this explains why there were no differences in baseline variables of self-rated health, self-reported walking ability or frailty between the institutionalized and not institutionalized participants, contrary to what we found in our previous work [ 12 ].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…By omitting the participants still living at home at the end of the follow-up period, we also ascertained that we had complete data on the participants’ acquired conditions during their lifetime. The excluded participants were, however, in better health than the included participants and this explains why there were no differences in baseline variables of self-rated health, self-reported walking ability or frailty between the institutionalized and not institutionalized participants, contrary to what we found in our previous work [ 12 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Other factors associated with a higher risk of institutionalization include higher age, living alone, low socioeconomic status, use of home care, low number of specialist visits, low self-rated health (SRH), low body mass index (BMI), cognitive and functional impairment including walking difficulties and falls, and several chronic conditions, such as Parkinson's disease, mood disorders, stroke and multimorbidity [4][5][6][7][8][9][10][11][12]. Among the oldest old women (> 90 years), Parkinson's disease, depression, hip fracture, and multimorbidity, in addition to dementia, predict a higher risk of institutionalization [13].…”
Section: Introductionmentioning
confidence: 99%
“…The LI did not predict institutionalization which seems to be better predicted with clinical FIs [1,16]. Routine laboratory parameters do not predict dementia or cognitive impairment which are considered the most common causes for institutionalization [28][29][30][31][32].…”
Section: Discussionmentioning
confidence: 82%
“…We have earlier demonstrated that clinical frailty tools are applicable screening instruments among Finnish community-dwelling older people [15,16]. Frailty was associated with higher mortality according to three different clinical frailty screening tools.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation